Butyrate Attenuates Lung Inflammation by Negatively Modulating Th9 Cells - Vieira, Raquel de Souza; Castoldi, Angela; Basso, Paulo José; Hiyane, Meire Ioshie; Câmara, Niels Olsen Saraiva; Almeida, Rafael Ribeiro (Frontiers in Immunology, 2019)
Th9 cells orchestrate allergic lung inflammation by promoting recruitment and activation of eosinophils and mast cells, and by stimulating epithelial mucus production, which is known to be mainly dependent on IL-9. These cells share developmental pathways with induced regulatory T cells that may determine the generation of one over the other subset. In fact, the FOXP3 transcription factor has been shown to bind il9 locus and repress IL-9 production. The microbiota-derived short-chain fatty acids (SCFAs) butyrate and propionate have been described as FOXP3 inducers and are known to have anti-inflammatory properties. While SCFAs attenuate lung inflammation by inducing regulatory T cells and suppressing Th2 responses, their effects on Th9 cells have not been addressed yet. Therefore, we hypothesized that SCFAs would have a protective role in lung inflammation by negatively modulating differentiation and function of Th9 cells. Our results demonstrated that butyrate is more effective than propionate in promoting FOXP3 expression and IL-9 repression. In addition, propionate was found to negatively impact in vitro differentiation of IL-13-expressing T cells. Butyrate treatment attenuated lung inflammation and mucus production in OVA-challenged mice, which presented lower frequency of lung-infiltrated Th9 cells and eosinophils. Both Th9 cell adoptive transfer and IL-9 treatment restored lung inflammation in butyrate-treated OVA-challenged mice, indicating that the anti-inflammatory effects of butyrate may rely on suppressing Th9-mediated immune responses.